A process for configuring technology management tools. (3rd January 2012) - Keltsch, JanNiklas; Probert, David; Phaal, Rob
This paper presents a process that managers apply when implementing technology management tools within their organisations. The results of the study suggests that the tool implementation is triggered by multiple events and followed by the four process phases of studying, configuring, executing and reconfiguring the tool. The study analyses bestpractice findings from industry cases and suggest activities for each process phase that managers should be aware of. These results are derived from a participant observer investigation and case studies conducted within 13 companies from various industry sectors.